Participation of Hageman Factor Dependent Pathways in Human Disease States - Colman, Robert W.; Wong, Patrick Y. (Thrombosis and Haemostasis, 1977)
Abnormalities of Hageman factor dependent pathways have been described in a wide variety of human disease states. Congenital deficiencies of factor XII (Hageman trait) prekallikrein (Fletcher trait) and high molecular weight kininogen (Williams, Fitzgerald and Flaujeac traits) although resulting in profound in vitro changes, do not cause in vivo difficulties. In contrast, deficiency of Cl esterase inhibitor (hereditary angioedema) results in significant morbidity and mortality. Acquired diseases may exhibit decreased synthesis of these three proteins in cirrhosis and dengue fever. In vivo activation of factor XII initiated pathways occur in septic shock, disseminated or localized intravascular coagulation, typhoid fever, polycythemia vera, hyperbetalipoproteinemia, coronary artery disease, nephrotic syndrome, transfusion reactions, hemodialysis and extracorporeal bypass. Activation of both the intrinsic system and tissue mediators contribute to the vasomotor phenomena in carcinoid syndrome and postgastrectomy dumping. Roles for factor XII, prekallikrein and kininogen have been suggested in gouty arthritis, allergic disorders and cystic fibrosis but the evidence is not yet convincing in these disorders.